2014
DOI: 10.1016/j.metabol.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality is associated with circulating C-reactive protein but not irisin levels in humans

Abstract: Objective Adherence to a healthy diet has been shown to decrease the incidence of obesity and associated comorbidities. C-reactive protein (CRP) is an established inflammatory marker and irisin was recently identified as a molecule which may play a role in energy regulation and obesity but whether diet alters irisin levels remains unknown. We aimed to investigate the association between circulating irisin, leptin, and CRP levels and dietary quantity and quality using the Alternate Healthy Eating Index (AHEI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 55 publications
(65 reference statements)
2
48
1
2
Order By: Relevance
“…In the other study, BMI levels of women were higher than the men (although not statistically signifi cant). Th e positive correlation between BMI and irisin has been shown in previous studies (Park et al 2014). As for its relation with age, the mean age of women in T1DM group of our study was fairly high compared to the other study.…”
Section: Discussionsupporting
confidence: 68%
“…In the other study, BMI levels of women were higher than the men (although not statistically signifi cant). Th e positive correlation between BMI and irisin has been shown in previous studies (Park et al 2014). As for its relation with age, the mean age of women in T1DM group of our study was fairly high compared to the other study.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, oxidative stress and inflammation, which are two mechanisms involved in the onset of insulin resistance [32], were associated with an increase in irisin levels, as was 6 reflected in human muscle [33] and liver [34]. However, the irisin effect appears to be exerted in a nutrition-independent fashion because its circulating levels were not associated with dietary indices [35].…”
Section: Introductionmentioning
confidence: 99%
“…Its level has been reported to be high in patients with insulin resistance (27), metabolic syndrome (28), and obesity (29), and low in cases of anorexia nervosa (30) and type 2 diabetes mellitus (31). Wen et al reported that the irisin level was lower in non-diabetic stage 5 CKD patients not on dialysis than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%